On dictionary definitions of selected Polish Anglicisms and their English etymons - Mańczak-Wohlfeld, Elżbieta (Papers in Linguistics, 2024)
It is generally agreed that in the process of borrowing both form and meaning are transferred from the donor language to the receptor. It is also assumed that in most cases fewer senses are transferred from the source language to the recipient tongue. The aim of the present paper is to analyze an arbitrarily chosen corpus consisting of the oldest Polish Anglicisms, namely those from the turn of the 18th and 19th centuries, in order to determine whether the above assumption is correct, as well as to compare the scope of the English and Polish definitions of the selected vocabulary items. The Polish lexemes are considered to be of English origin on the basis of present-day knowledge. Their definitions have been attested in two comparable large dictionaries, i.e. those which include over 100,000 entries: The Concise Oxford Dictionary of Current English (2011) and Uniwersalny słownik języka polskiego (2010).